Design of Continuous Composite Road Bridges - Bridge girders with corrugated webs in stainless steel - ÖMAN, MICHAELA; STEFFNER, JULIA (My University, 2021)
Continuous steel/concrete composite bridges are a commonly used bridge solution normally designed with steel girders with flat webs in carbon steel. Carbon steel is susceptible to corrosion and demands repeated maintenance. By using stainless steel instead, the maintenance can be reduced. Due to higher material cost for stainless steel it is of importance to use innovative methods to minimize the mate rial consumption. Girders with corrugated webs provide higher shear capacity than conventional beams with flat-webs which can be interpreted as reduction in web thickness and number of vertical stiffeners. As a result, the weight of the girders and the associated production costs could be reduced. The aim of the study is to investigate the possibilities to optimize the design of continuous composite stainless steel/concrete girders using corrugated webs and to show possible material savings that can be obtained using this concept. The savings are investigated in terms of investment costs, maintenance costs and environmental impact. In order to investigate the different concepts, finite element models are created in Brigade/Plus. The models are based on Python-scripts that are built up as a general design tool in order to generate different design concepts. Two case studies are performed in order to compare the concepts with girders with flat webs in carbon steel to girders with corrugated webs in stainless steel. The results indicate that both the higher material strength of stainless steel and the increased load-bearing capacity of girders with corrugated webs contribute to up to 19% material savings in the studied cases. According to the case studies, higher beams lead to larger material savings since the corrugation can be better utilized. For lower beams the material savings are more dependent on the material strength than the corrugation. Comparing the concept of flat webs with carbon steel to corrugated webs in stainless steel showed that the investment cost is only marginally higher for the concept with stainless steel. The total cost including both investment and maintenance cost are on the other hand lower for the design with corrugated webs in stainless steel. This is due to the high maintenance costs for carbon steel bridges. The calculated carbon emissions are higher for the bridges designed with flat webs in carbon steel compared to corrugated webs in stainless steel. This is mainly due to higher material consumption for the designs with flat webs in carbon steel.
Keywords: Composite bridges, Continuous bridges, Stainless steel, Corrugated web.